2017
DOI: 10.1186/s12960-016-0176-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with occupancy of pharmacist positions in public sector hospitals in Uganda: a cross-sectional study

Abstract: BackgroundPharmacists are invaluable resources in health care. Their expertise in pharmacotherapy and medicine management both ensures that medicines of appropriate quality are available in health facilities at the right cost and are used appropriately. Unfortunately, some countries like Uganda have shortage of pharmacists in public health facilities, the dominant providers of care. This study investigated the factors that affect the occupancy of pharmacist positions in Uganda’s public hospitals, including hir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
71
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(74 citation statements)
references
References 20 publications
2
71
0
Order By: Relevance
“…This raises questions about how this process could be speeded up. The importance of tailored support programs is emphasized here and in other studies [ 36 , 37 ]. Initiatives in Sweden, the so-called “fast track,” are trying to help immigrants with a university education, including IENs and IMGs, find employment.…”
Section: Discussionmentioning
confidence: 70%
“…This raises questions about how this process could be speeded up. The importance of tailored support programs is emphasized here and in other studies [ 36 , 37 ]. Initiatives in Sweden, the so-called “fast track,” are trying to help immigrants with a university education, including IENs and IMGs, find employment.…”
Section: Discussionmentioning
confidence: 70%
“…This has implications for the need for collaboration and financial allocation from other sectors. CHWs, positioned at the interface between the community and the health system, are potentially key actors in the process of pursuing UHC both in terms of extending services and as ‘agents of change’ with regard to social determinants as culturally and socially embedded members of their community ( R McCollum et al 2016 ; Kok et al 2017 ). They will require support from their community and health system to enable this ( Kok et al 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…With the exception of those who work in regulation and the pharmaceutical industry, most of the pharmacists in Uganda are in dual practice-working as the supervising pharmacist in more than one pharmacy at the same time. 18 Initially, dual pharmacy practice was permitted by PSU as a measure to cope with the small number of pharmacists and as an incentive to promote pharmacists taking up job positions in academia and public service as these sectors were unattractive to pharmacists mainly because of low pay. A study found 60% of pharmacists interviewed had ever applied for public hospital jobs, but 30% of them declined the jobs and 41% of those who accepted had since quit the job.…”
Section: Pharmacy Education and Practice In Ugandamentioning
confidence: 99%
“…A study found 60% of pharmacists interviewed had ever applied for public hospital jobs, but 30% of them declined the jobs and 41% of those who accepted had since quit the job. 18 PSU is now working toward reversing dual practice which is due to take effect in 2021, an action which may also increase the desirability of hospital pharmacy jobs, which are more secure and have higher pay than a single community pharmacy position.…”
Section: Pharmacy Education and Practice In Ugandamentioning
confidence: 99%